The competitiveness of small household pig producers in Vietnam: Significant research and policy findings from an ACIAR-sponsored study and their limitations - Tisdell, C.A. (University of Queensland, 2010)
The preamble to this paper highlights some of the major policy issues facing Vietnam as far as its supply of pork is concerned, in particular, the problem of its demand for pork rising at a faster rate than its supply. Some relevant background to this research project is provided by outlining selected features of Vietnam’s pig industry. Then the main findings (in the view of the author) from this ACIAR-funded research are presented. These results include (1) natural protection given to Vietnam’s pig producers from imports as a result of the nature of the preferences of Vietnamese consumers: (2) the importance of household labour, especially that provided by females, in the husbandry of pigs held by households; (3) the existence, or otherwise, of scale economies as a function of the number of pigs held by households and the economic efficiency of small producers, (4) the import dependence for pig food of Vietnam’s pig industry and the way in which it varies with the number of pigs kept by households; (5) specialization in pig production, (6) regional differences in the economics of pig production; (7) economic discrimination in the supply of inputs to household producers of pigs and in their sale of pigs; (8) the size of pig-holdings and the use of professional services, such as veterinary services and extension services; and (9) findings about miscellaneous matters, such as the genetic composition of the pig stock. Scope for future research in relation to these aspects is also highlighted, and the need is raised for considering the economics of increasing quality standards and certifying the quality of pork. The economics of increasing the scale of pig producing units is given particular attention. Vietnam’s policy options for improving the balance between its demand for pork and its supply are considered and the important role that household (small producers) have and can play in this regard are highlighted.